2009
DOI: 10.1097/gme.0b013e3181a037ed
|View full text |Cite
|
Sign up to set email alerts
|

Initial laparoscopic access in postmenopausal women

Abstract: Results of this preliminary comparison on the DOA and the Veress methods, commonly used by gynecologists, suggest that the visual entry system offers a statistical advantage over the closed Veress needle approach, in terms of time saving and limiting minor vascular injuries, thus enabling a safe and fast visually guided entry in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…8 In some instances, our results agreed with the results of comparative studies of DOE and VNE in reproductive-age women without previous surgery 6 and in postmenopausal women. 7 Furthermore, our results concurred with entry times by other teams 14 who applied DOE as an alternative to VNE in 650 laparoscopic procedures and who analyzed the site, the duration of entry, and any complications. String et al 14 demonstrated varied mean entry times in seconds with SD values depending on the trocar entry sites: 114 ± 30 at the back site, 92 ± 45 at the umbilical site, and 77 ± 35 at remaining sites, including right/left/midline upper and right/left lower quadrants, with 2 serious complications such as small-bowel and gallbladder injuries.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…8 In some instances, our results agreed with the results of comparative studies of DOE and VNE in reproductive-age women without previous surgery 6 and in postmenopausal women. 7 Furthermore, our results concurred with entry times by other teams 14 who applied DOE as an alternative to VNE in 650 laparoscopic procedures and who analyzed the site, the duration of entry, and any complications. String et al 14 demonstrated varied mean entry times in seconds with SD values depending on the trocar entry sites: 114 ± 30 at the back site, 92 ± 45 at the umbilical site, and 77 ± 35 at remaining sites, including right/left/midline upper and right/left lower quadrants, with 2 serious complications such as small-bowel and gallbladder injuries.…”
Section: Discussionsupporting
confidence: 87%
“…Over the years, we have been researching abdominal entry with comparative studies of direct optical entry (DOE) using a bladeless trocar versus a blind closed access by Veress needle entry (VNE) in young women without previous surgery, 6 in postmenopausal women, 7 as well as comparison of DOE with open laparoscopy by open Hasson technique (OHT) in women with previous abdominopelvic surgery. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation